Application of laser scanners on Earth - Zhuparkhanovyna B, Жұпарханқызы Б; Alduashova K.M., Алдуашова К.М. (Рroblems of engineering and professional education, 2023)
This article contains accurate and complete information about the objects of laser scanners that are widely used today